The Effect of Work Competency, Work Motivation, And Organizational Citizenship Behavior (OCB) On Organizational Commitment and Employee Performance at PT. Bina Ceria Bersama In Surabaya - Shientha Noer Iswibiarka Wibowo; I Dewa Ketut Raka Ardiana; Tri Andjarwati (Green Publisher Indonesia, 2023)
The purpose of this research is to analyze and interpret the influence of work competencies, work motivation, and organizational citizenship behavior on the organizational commitment and performance of employees of PT. Bina Ceria Bersama in Surabaya. The results in the study suggest that 1) Work competency has a significant effect on the organization's commitment to employees of PT. Bina Ceria Bersama in Surabaya. 2) Work motivation has a significant effect on the organization's commitment to the employees of PT. Bina Ceria Bersama in Surabaya. 3) Organizational Citizenship Behavior has a significant effect on the organization's commitment to employees of PT. Bina Ceria Bersama in Surabaya. 4) Work competency has a significant effect on employee performance at PT. Bina Ceria Bersama in Surabaya. 5) Work motivation has no significant effect on employee performance at PT. Bina Ceria Bersama in Surabaya. 6) Organizational Citizenship Behavior has no significant effect on employee performance at PT. Bina Ceria Bersama in Surabaya. 7) The organization's commitment has a significant impact on employee performance at PT. Bina Ceria Bersama in Surabaya